Transcriptome and Small RNA Combined Sequencing Analysis of Cold Tolerance in Non-heading Chinese Cabbage - Wang, Jin; Zhang, Qinxue; You, Xiong; Hou, Xilin (Frontiers in Genetics, 2021)
Background: Non-heading Chinese cabbage (Brassica rapa ssp. chinensis) is an important leaf vegetable grown worldwide. However, there has currently been no enough transcriptome and small RNA combined sequencing analysis of cold tolerance, which hinders further functional genomics research. Results: In this study, 63.43 Gb of clean data was obtained from the transcriptome analysis. The clean data of each sample reached 6.99 Gb, and the basic percentage of Q30 was 93.68% and above. The clean reads of each sample were sequence aligned with the designated reference genome (Brassica rapa, IVFCAASv1), and the efficiency of the alignment varied from 81.54% to 87.24%. According to the comparison results, 1,860 new genes were discovered, of which 1,613 were functionally annotated. Among them, 13 common differentially expressed genes were detected in all materials, including 7 up-regulated and 6 down-regulated. At the same time, we used quantitative real-time PCR to confirm the changes of these gene expression levels. In addition, we sequenced miRNA of the same material. Our findings revealed a total of 34,182,333 small RNA reads, 88,604,604 kinds of small RNAs, among which the most common size was 24 nt. In all materials, the number of common differential miRNAs is 8. According to the corresponding relationship between miRNA and its target genes, we carried out Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analysis on the set of target genes that each group of differentially expressed miRNAs. Through the analysis, it is found that the distributions of candidate target genes in different materials are different. We not only use transcriptome sequencing and small RNA sequencing, but also use experiment to prove the expression levels of differentially expressed genes that were obtained by sequencing. Sequencing combined with experiments proved the mechanism of some differential gene expression levels after low temperature treatment. Conclusions: In all, this study provides a resource for genetic and genomic research under abiotic stress in Pak-choi.